KONSTRUKSI PRIORITAS PEMBANGUNAN DALAM RPJMD PROVINSI SULAWESI SELATAN DAN SULAWESI TENGGARA: ANALISIS KOMPARATIF PERSPEKTIF GOVERNANCE - Andi Rahmat Nizar Hidayat; Misbahuddin (Journal of Contemporary Public Administration, 2026)
The paradigm shift in public administration from government to governance has encouraged local governments to move beyond merely administrative management toward development that is collaborative , adaptive, and oriented toward public value. In this context, the Regional Medium-Term Development Plan (RPJMD) is understood not merely as a technocratic document, but as a political and governance construction reflecting how local governments frame development issues, determine policy priorities, and build public legitimacy. This study aims to analyze the construction of development priorities in the RPJMDs of South Sulawesi Province and Southeast Sulawesi Province for the 2025–2029 period from a governance perspective. The research employs a qualitative approach with a comparative document study design. The primary data consist of RPJMD and RPJPD documents from both provinces, which were analyzed using interpretive policy analysis to identify the framing of development issues, policy orientations, actor representations, and public values embedded in regional development narratives. The findings reveal that South Sulawesi constructs development within a structural transformation framework emphasizing regional competitiveness, territorial connectivity, investment, industrial downstreaming, and development innovation. The emerging governance model tends toward strategic–collaborative  governance, characterized by expanding collaboration between government and non-state actors. In contrast, Southeast Sulawesi constructs development priorities based on its archipelagic characteristics, focusing on equitable development, inter-island connectivity, reduction of spatial disparities, and natural resource management aimed at community welfare. The governance model reflected is more territorial–distributive governance, marked by the dominant role of the state in regional development. The novelty of this study lies in positioning the RPJMD as a subnational governance construction, demonstrating that decentralization produces contextual and varied regional governance typologies shaped by each region’s characteristics. These findings highlight the importance of participatory, inclusive, and sustainability-oriented RPJMD formulation.